The revival of protectionism - Corden, W. M. (New York : Group of Thirty, 1984)
The paper deals with the revival or intensification of protectionism in developed countries since the first oil crisis at the end of the great postwar boom in 1973. It focuses on macroeconomic aspects, and especially on the relationship between protection and exchange rate.
Occasional papers 14
Includes bibliographical references.
osc 11/07/2018
Loans
Keywords: Protectionism